Diagnostic Accuracy of Spot Urine Protein-Creatinine Ratio in Women with Pre-Eclapmsia (Medical Forum Monthly, 2024)
Objective: To determine the diagnostic accuracy of spot urine protein-creatinine ratio in women with pre-eclampsia as compared with 24-hr urine protein excretion.Study Design: Descriptive / cross-sectional studyPlace and Duration of Study: This study was conducted at Obstetrics and Gynecology Department of Liaquat University Hospital, Hyderabad for duration of one year from February 20, 2015 to February 19, 2016.Materials and Methods: Subjects for this study were collected by using non-probability consecutive sampling technique Women of all parity having systolic blood pressure (SBP) ≥140 mmHg or a diastolic BP (DBP) ≥90 mmHg were included for this study. Women with medical disorders like renal disease, diabetes mellitus, were excluded.Information regarding demographic data, medical history, obstetrical history, general physical examination and ultrasonography were recorded. A spot mid-stream urine sample was obtained from every patient afterthat 24-hour urine collection was started. Patients having confirmed proteinuria were considered and treated for pre-eclampsia. All information were recorded on a predesigned proforma. SPSS version 16.0 was used for data analysis.Results: Total 404 pregnant hypertensive women were included in this study. The mean±SD age of the subjects was 27.08±5.84 years. The mean±SD systolic blood pressure of the subjects was 161.68±19.59 mmHg, whereas the mean±SD diastolic blood pressure of the subjects was 104.70±12.65 mmHg on dipstick test 140 (34.7%) presented with 1+. The results of 24-hours urine collection showed that 158 (39.1%) subjects were negative for proteinuria while urine protein-creatinine ratio revealed that 358 (88.6%) subjects were positive for preeclampsiaConclusion: The present study indicates that for the clinical purposes, spot urine protein-creatinine ratio is a satisfactory and reliable substitute for determination of proteinuria than in a 24 hour urine collection.